A Novel Rodent Orthotopic Forelimb Transplantation Model That Allows for Reliable Assessment of Functional Recovery Resulting From Nerve Regeneration. Issue 3 (12th September 2016) - Kern, B.; Budihardjo, J. D.; Mermulla, S.; Quan, A.; Cadmi, C.; Lopez, J.; Khusheim, M.; Xiang, S.; Park, J.; Furtmüller, G. J.; Sarhane, K. A.; Schneeberger, S.; et al.
Abstract : Improved nerve regeneration and functional outcomes would greatly enhance the utility of vascularized composite allotransplantation (VCA) such as hand and upper extremity transplantation. However, research aimed at achieving this goal has been limited by the lack of a functional VCA animal model. We have developed a novel rat midhumeral forelimb transplant model that allows for the characterization of upper extremity functional recovery following transplantation. At the final end point of 12 weeks, we found that animals with forelimb transplantation including median, ulnar and radial nerve coaptation demonstrated significantly improved grip strength and forelimb function as compared to forelimb transplantation without nerve approximation (grip strength: 1.71N ± 0.57 vs. no appreciable recovery; IBB scale: 2.6 ± 0.7? vs. 0.8 ± 0.40; p = 0.0005), and similar recovery to nerve transection‐and‐repair only (grip strength: 1.71N ± 0.57 vs. 2.03 ± 0.42.6; IBB scale: 2.6 ± 0.7 vs. 2.8 ± 0.8; p = ns). Moreover, all forelimb transplant animals with nerve coaptation displayed robust axonal regeneration with myelination and reduced flexor muscle atrophy when compared to forelimb transplant animals without nerve coaptation. In conclusion, this is the first VCA small‐animal model that allows for reliable and reproducible measurement of behavioral functional recovery in addition to histologic evaluation of nerve regeneration and graft reinnervation. Abstract : A novel rodent orthotopic forelimb transplantation model allows for reliable and reproducible measurement of functional recovery of an upper extremity transplant by measuring progressive return of grip strength and evaluating component upper extremity motions of the transplant via video tracking and a standardized scaling system. See the supplemental video at amjtransplant.com/videos.